Experimental Mathematics. Volume 15, Number 4, 2006 - A K Peters (A K Peters, 2009)
Artin's Conjecture, Turing's Method, and the Riemann Hypothesis Full TextPDF (480.6 KB) Author Andrew R. Booker 385-407